Simplifying means things like 2q + 4q = 6q. In that question, it just means find the answer.
1 + (1/3) = 4/3
1 - (3/7) = 4/7
(4/3) / (4/7) = 7/3
2007-12-08 09:15:13
·
answer #1
·
answered by haydenriach 2
·
0⤊
0⤋
Er...okay...in this case:
1) work on the fraction first. for now, don't do anything with the 1, the 1 being a whole number that will affect the fraction after it is simplified.
2)work with 1/3/1-3/7:
a) first, deal with the 1-3/7. You will have to use this to divide with, but you can't do it unless that is resolved, since it's actually like this: 1/3 divided by (1-3/7). So, 1-3/7=7/7-3/7=4/7
b) Back to the last section with the division: 1/3/4/7. Next, divide 1/3 and 4/7: 1/3 / 4/7=1/3 * 7/4= 7/12. [when dividing, the reciprocal of the second fraction is multiplied with the first]
3) Now you can finish with the 1: 1+7/12=12/12+7/12=19/12.
I hope this helps.
2007-12-08 09:23:46
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
1+1/3 / 1-3/7= 4/3/ 4/7=4/3*7/4= the 2 4's cancel out= 7/3
2007-12-08 11:20:54
·
answer #3
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
1 + (1/3) = 4/3
1 - (3/7) = 4/7
(4/3) / (4/7) = 7/3
2007-12-08 09:49:40
·
answer #4
·
answered by UNIQUE 3
·
0⤊
0⤋
10
2007-12-08 09:32:05
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
(1+(1/3))/(1-(3/7))
((3/3)+(1/3))/((7/7)-(3/7)) for 1=(a/a)
((3+1)/3)/((7-3)/7)) for (a/c)+(b/c)=(a+b)/c
(4/3)/(4/7)
(1/3)/(1/7) for (a/b)/(a/c)=(1/b)/(1/c)
(7/3) for (1/a)/(1/b)=(b/a)
2007-12-08 09:16:28
·
answer #6
·
answered by capt.harkness 1
·
0⤊
0⤋
(1 + 1/3) is the same as 3/3 + 1/3 or 4/3
(1 - 3/7) is the same as 7/7 - 3/7 or 4/7
So:
4/3 / 4/7
Or flip one fraction upside down and multiply the tops and bottoms:
4/3 * 7/4 = 28/12
or 2 4/12
or 2 1/3
BTW, the answer to your question of "simplify" isn't 2 1/3 but:
4/3 / 4/7
2007-12-08 09:12:29
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋
You mean (1+1/3) / (1-3/7), right?
Multiply top and bottom by 21 (LCD)
(21 + 7)/(21 - 9)
28/12
7/3
2007-12-08 09:12:06
·
answer #8
·
answered by ben e 7
·
0⤊
0⤋
-4 * - 1x = 4x The two negatives cancel, making it positive. 4x(x^2) = 4x^3 4x is also known as 4x^1, the one is never written as it has no affect on the number. Make sense?
2016-04-08 02:06:07
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
1+.33333-.42857
now you can do it
plz choose mine as best answer
2007-12-08 09:11:18
·
answer #10
·
answered by Anonymous
·
0⤊
2⤋